MKK7 and ARF: new players in the DNA damage response scenery - Kotsinas, Athanassios; Papanagnou, Panagiota; Galanos, Panagiotis; Schramek, Daniel; Townsend, Paul; Penninger, Josef M; Bartek, Jiri; Gorgoulis, Vassilis G (Cell Cycle, 2014)
Sensing, integrating, and processing of stressogenic signals must be followed by accurate differential response(s) for a cell to survive and avoid malignant transformation. The DNA damage response (DDR) pathway is vital in this process, as it deals with genotoxic/oncogenic insults, having p53 as a nodal effector that performs most of the above tasks. Accumulating data reveal that other pathways are also involved in the same or similar processes, conveying also to p53. Emerging questions are if, how, and when these additional pathways communicate with the DDR axis. Two such stress response pathways, involving the MKK7 stress-activated protein kinase (SAPK) and ARF, have been shown to be interlocked with the ATM/ATR-regulated DDR axis in a highly ordered manner. This creates a new landscape in the DDR orchestrated response to genotoxic/oncogenic insults that is currently discussed.
Keywords: signální transdukce; Animals; Humans; Phosphorylation; ATM protein; lidé; Reading Frames; zvířata; Signal Transduction; čtecí rámce; DNA Repair; mitogenem aktivované proteinkinasy p38; Ataxia Telangiectasia Mutated Proteins; p38 Mitogen-Activated Protein Kinases; Oncogenes; oprava DNA; DNA Damage; MAP kinasa-kinasa 7; nádorový supresorový protein p53; Tumor Suppressor Protein p53; MAP Kinase Kinase 7; poškození DNA; onkogeny; fosforylace